Financial Disclosure Timeliness and Stock Market Reaction to Accounting Information (gjstudies, 2025)
This research introduces a novel methodological framework that reconceptualizesthe relationship between financial disclosure timeliness and market efficiency by integrating principles from quantum-inspired information theory with behavioral finance.Traditional studies have examined disclosure timing through linear regression models,but this approach fails to capture the complex, non-linear dynamics of information absorption in modern markets. Our study proposes that disclosure timeliness functionsnot as a simple temporal variable but as a quantum-like superposition of information states that collapse upon market observation, creating unique patterns of pricediscovery. We develop a Quantum-Informed Market Absorption (QIMA) model thattreats accounting disclosures as information packets with inherent latency characteristics that interact with market microstructure in ways that conventional models cannotadequately represent. Through analysis of high-frequency trading data from threemajor stock exchanges over a five-year period, we demonstrate that early disclosurescreate information asymmetries that persist in market memory far longer than previously documented, while late disclosures trigger cascading volatility effects that followpower-law distributions rather than normal distributions. Our findings reveal that themarket’s reaction coefficient to accounting information varies by a factor of 2.7 between optimally-timed and poorly-timed disclosures, with the most significant effectsobserved in earnings announcements that coincide with quantum-inspired ’resonanceperiods’ in market attention cycles. This research contributes to accounting literatureby providing the first evidence that disclosure timeliness affects not only the magnitude but the fundamental nature of market reactions, transforming our understanding of how temporal information properties shape financial market behavior.